Shear strength of RC columns under multi-directional loading - Paulus Irawan (2008)
In recent years, some reinforced concrete (RC) columns in high-rise buildings, bridges and elevated highways suffered severe damage during strong earthquakes due to brittle and catastrophic shear failure. Under seismic loads, depending on the direction of the ground motion and the connection between the columns and other members, these columns can experience any combination of shear force, axial force, bending moment and torsion. The disastrous collapse of RC columns during the earthquakes motivates a study on the behaviour of RC short columns subjected to multi-directional forces, typical of seismic or wind load.